Is Economic Theory, Presented in Basic Academic Textbooks, Applicable to the Digital Economy? - Vujica Lazovic (MDPI AG, 2021)
With the aim of improving modern methods for educating economists, the authors in this paper impose the following topics: What do we want to teach students, and do we teach them the right things? How transformative are our fundamental textbook bases to offer the new knowledge that the digital economy imposes? Bearing in mind previous questions, the aim of this paper is to highlight the gap that exists between economic theory and economic practice in terms of insufficient theoretical scope of the digital economy (DE) and its study, and DE’s increasing participation in global practice as an economy based on innovation and new technologies. In the analysis, the authors concentrate on two levels: (1) they analyse the specifics of DE and in that context, they evaluate the applicability of traditional economic theory; (2) they review the representation of DE in university textbooks. Based on the results, the authors conclude that DE possesses specific attributes, and it is necessary to include these as mandatory lessons in university textbooks on the level of basic studies. They suggest some areas for which economic theory should be better explained and supplemented in future research (proposing appropriate guidelines for future efforts in theoretical work). Moreover, through a systematic literature review, the authors approach 90 basic university textbooks in economics and by analysing their content, they prove that DE is not sufficiently represented in them. The results of the paper suggest that economics textbooks, and thus the curricula of basic studies, should be supplemented with chapters on the digital economy, which will affect the modernization and adequacy of theory with practice.